Fructose regulates M1 macrophage polarisation by promoting glycolysis - WANG Minghong; LIU Yubing; WANG Xinhang; LI Han; CHEN Sihong; ZHANG Minhua; PENG Yang; LU Cailing; TANG Shen; LI Xiyi (Guangxi Yike Daxue xuebao)
Objective To investigate the regulatory effect of fructose (Fru) on the polarization of M1 macrophages induced by lipopolysaccharide (LPS) and interferon gamma (IFN-γ) and its possible mechanism. Methods The experiment was divided into M0 group (THP-1 cells were stimulated with 100 nmol/L phorbol esters for 24 h), M1 group (M0 group was stimulated with 10 ng/mL LPS and 20 ng/mL IFN-γ for 48 h), and M1+5 mmol/ L Fru group (5 mmol/L Fru was added simultaneously with LPS and IFN- γ for 48 h of stimulation). Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to detect the mRNA expression of polarization markers interleukin-1β (IL-1β), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and cyclooxygenase-2 (COX-2) in M1 macrophages. The activities of glycolytic rate-limiting enzyme hexokinase (HK) and lactate dehydrogenase (LDH) were detected using a microenzyme activity kit. The reactive oxygen species (ROS) kits were used to detect intracellular ROS levels. The phagocytic ability of the cells was detected by neutral erythrophagocytosis assay. The mitochondrial respiratory chain metabolic enzyme activities were detected by Azulin method. The adenosine triPhosphate (ATP) contents were detected by using an ATP test kit. Results Compared with the M0 group, mRNA expression of IL-1β, IL-6, TNF-α and COX-2 in the M1 group was increased, activities of HK and LDH were increased, mitochondrial respiratory chain metabolic enzyme activities and ATP contents were decreased, intracellular ROS production was increased, and phagocytic ability was enhanced (all P < 0.05). Compared with the M1 group, mRNA expression levels of IL-1β, IL-6, TNF- α and COX-2 in the M1+5 mmol/L Fru group were increased, activities of HK and LDH were increased, mitochondrial respiratory chain metabolic enzyme activities and ATP contents were decreased, intracellular ROS production was increased, and phagocytic ability was decreased (all P < 0.05). Conclusion Fructose may promote the glycolysis of M1 macrophages, reduce the level of oxidative phosphorylation, upregulate the expression of polarization related markers of M1 macrophages, promote the production of ROS, and downregulate the phagocytic ability of macrophages, thereby regulating the polarization of M1 macrophages.